Stephen Stills change partners - Roberts, David 1954- (Red Planet, 2016)
During his six-decade career, Stephen Stills has been the driving force behind Buffalo Springfield, Crosby, Stills & Nash, Crosby, Stills, Nash & Young, Manassas and The Rides: to date, he remains the only person to have been inducted twice in one night into The Rock and Roll Hall of Fame. This biography traces the life and career of the prolific singer-songwriter who has collaborated with Jimi Hendrix, Eric Clapton, Jimmy Page, Joni Mitchell, Ringo Starr, Judy Collins, Rita Coolidge and Public Enemy, to name but a few
"The definitive biography" -- Cover
Keywords: Stills, Stephen -- 1945-; Geschichte 1945-; Rockmusiker; USA; Stills, Stephen; Rock musicians / United States / Biography; Biographies; Biografie